Connectivity of CPEC with Afghanistan and its Implications for the Region - Sami Ullah; Mekhraj Khan; Kifayat Ullah (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The China-Pakistan Economic Corridor (CPEC), which would span a distance of 2700 km and link the Chinese city of Kashgar with Pakistan’s deep-sea port of Gwadar in Baluchistan, bordering Afghanistan, is the centerpiece project of Belt and Road Initiative (BRI). Due to its political, economic, and security interests in Afghanistan, China has a great interest to connect CPEC with Afghanistan. The regional states will have great economic opportunities in this connectivity. CPEC project is a blessing for the whole region especially for landlocked central Asian countries and Afghanistan. Furthermore, it will promote regional integration, which will increase trade and economic activity within the region. This study tries to examine CPEC’s connectivity with Afghanistan and its implications for the area while keeping in mind how significant it is. In this study, both descriptive and analytical approaches have been used. The current study is qualitative in nature and secondary sources have been used for the completion of this research paper. This study came to the conclusion that CPEC’s link with Afghanistan is crucial and will support the local economy.